2016
DOI: 10.1017/s1049096515001122
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Breakout Sessions on Student Success and Satisfaction

Abstract: Introductory American government is a common component of college and university core curricula and, as such, it often is taught in large sections. This makes active learning more diffi cult, which may contribute to student dissatisfaction and lower levels of student achievement. In turn, this can aff ect larger issues of university retention. This article considers whether different models of instruction in large classes affect student success and satisfaction. We compare a lecture-only class and one that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The introduction of SPA alleviated this underscripting in all but two of the teams. The results support the idea that at least some of the problems previously observed in breakout rooms (e.g., lack of success and satisfaction (Blackstone and Oldmixon, 2016;) dissatisfaction in higher-GPA students (Lougheed et al, 2012)) can be attributed to lack of structure and underscripting.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The introduction of SPA alleviated this underscripting in all but two of the teams. The results support the idea that at least some of the problems previously observed in breakout rooms (e.g., lack of success and satisfaction (Blackstone and Oldmixon, 2016;) dissatisfaction in higher-GPA students (Lougheed et al, 2012)) can be attributed to lack of structure and underscripting.…”
Section: Discussionsupporting
confidence: 85%
“…There are also some indications that breakout rooms do not always magically create engagement and higher levels of learning. Blackstone and Oldmixon (2016) found that students in a breakout from a lecture class were not more satisfied and did not succeed at higher levels compared to their peers in a lecture-only class. Lougheed et al (2012) found that higher-GPA students had a significantly less favorable response to the use of breakout groups than did their lower-GPA colleagues.…”
Section: Use Of Breakout Rooms In Online Learningmentioning
confidence: 88%
“…Both classes were taught by the same instructor and were of similar size (200+ students). To the researchers' surprise, they found that students in the class with breakout groups were less satisfied and less successful in terms of course grades, compared to the students in the lectureonly class [3]. They state that flaws in the study design as well as poor attendance rates in the class with breakout groups may have contributed to this unpredicted finding.…”
Section: Related Workmentioning
confidence: 97%
“…Although quite different from a virtual setting, the findings from some of these studies are still interesting to take note of. Blackstone and Oldmixon [3] compared student success and satisfaction between a traditional lecture-only class to a class that used breakout groups. Both classes were taught by the same instructor and were of similar size (200+ students).…”
Section: Related Workmentioning
confidence: 99%
“…First, they immerse students in real-life situations and help them to evaluate complex concepts and to think strategically (Bromley 2013; Glasgow 2015; Omelicheva and Avdeyeva 2008; Switky 2014; Trueb 2013). This immersive experience encourages students to explore diverse perspectives (Nance, Suder, and Hall 2016; Switky 2014) while also helping them to identify their own assumptions (Blackstone and Oldmixon 2016; Bromley 2013, 820; Switky 2014). Second, active-learning strategies enable students to use their diverse lived experiences to inform one another’s understanding of course material (Asal 2005; King and Sen 2013; Macauley 2016), which can be difficult to facilitate in traditional lectures.…”
Section: Pedagogical Context: Challenges and The Strategymentioning
confidence: 99%